Correction of the psychophysiological state of professional musicians by means of physical culture - V.K. Klimova,; Yu.V. Filippova,; L.K. Buslovskaya,; E.V. Strizhakova, (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop and test a set of exercises to correct the psychophysiological state of professional musicians. Methods and structure of the study. The participants of the experiment were professional orchestral musicians of the string-plucked group of the Russian folk orchestra during the period of intense concert activity. The diagnostics of well-being was carried out using the methods of observation and questioning. A quantitative assessment of the components of health and health in general has been determined. Based on the information received, sets of exercises were compiled, recommended for carrying out during breaks in the process of rehearsal work. Results and conclusions. It has been established that the introduction of the proposed complex of physical exercises into the structure of the rehearsal process increases the indicator of the quantitative assessment of the components of health and general health, delays the onset of fatigue, and reduces pain in the back and hands.